Hepatic Arterial Infusion Chemotherapy With Folfirinox or Oxaliplatin Alone in Metastatic Colorectal Cancer - Randrian, Violaine; Pernot, Simon; Sionneau, Baptiste; Smith, Denis; Lim, Annie; Touchefeu, Yann; Gallois, Claire; Turpin, Anthony; Javed, Sahir; Guimbaud, Rosine; Rivera, Pascale; Karoui, Mehdi; et al. (Frontiers in Medicine, 2022)
Background Hepatic arterial infusion (HAI) of chemotherapy is an option for the treatment of patients with liver metastases from colorectal cancer (LMCRC). Though HAI with oxaliplatin (HAI-Ox) is generally used, 5FU-oxaliplatin-irinotecan HAI (HAI-Folfirinox) is feasible and leads to curative intent surgery in 30% of pretreated patients. We compared the efficacy and safety of HAI-Ox and HAI-Folfirinox. Methods Patients undergoing HAI chemotherapy for LMCRC were retrospectively included from 2008 to 2019 from six French expert centers. Results Data were collected from 273 previously treated patients with LMCRC. Patients received HAI-Folfirinox (n=52) or HAI-Ox (n=221) combined with IV chemotherapy. The objective response rate was 43.2% in HAI-Folfirinox patients and 45.9% (ns) in HAI-Ox patients. Median overall survival (OS) was 17 months (95% CI: 15-32.3) with HAI-Folfirinox and 26.2 months (95% CI: 19.4-34.4; p = 0.1) with HAI-Ox. Median progression-free survival (PFS) was 7.9 months (95% CI: 4.9-10,3) with HAI-Folfirinox and 6.4 months (95% CI: 6.0-7.7; p = 0.6) with HAI-Ox. The secondary liver resection rate was 35.6% with HAI-Folfirinox and 16.7% with HAI-Ox (p = 0.007). Grade 2 and above toxicities were significantly more frequent with HAI-Folfirinox. In the global population, only 2 factors were prognostic for OS in multivariable analyses: liver-only disease (HR:0.4; 95% CI 0.20-0.83; p = 0.013) and local complications of the catheter (HR:3.8; 95% CI 1.6-9.0; p = 0.002). Conclusions HAI results in high response rates, secondary resections and long survival in pretreated patients with LMCRC.